Failure to perceive clinical events: an under-recognised source of error. - Greig, P; Higham, H; Nobre, A (2014)
INTRODUCTION: Attentional focus narrows as individuals concentrate on tasks. Missing an event that would otherwise appear obvious is termed a perceptual error. These forms of perceptual failure are well-recognised in psychological literature, but little attention has been paid to them in medicine. Cognitive workload and expertise modulate risk, although how these factors interplay in practice is unclear. This video-based experiment was designed to explore the hypothesis that perceptual errors affect clinicians. METHODS: 142 volunteers with varying levels of experience of adult resuscitation were shown a short video depicting a simulated cardiac arrest. This video included a series of change-events designed to elicit perceptual errors. The experiment was conducted on-line, with participants watching the video and then responding via combinations of open-ended free-text and directed questioning. RESULTS: 141 people experienced at least a single perceptual error. Even the most clinically significant event (disconnection of the patient's oxygen supply) was missed by three in four viewers. Although expertise was associated with increased likelihood of detecting an occurrence, even highly significant events were missed by up to two thirds of the most experienced observers. DISCUSSION: This study demonstrates, for the first time, that perceptual errors occur during healthcare-relevant scenarios at significant levels. Events such as an oxygen malfunction would meaningfully affect patient outcome and, although expertise conferred some advantages, events were still missed more often than not. Data acquisition is fundamental to good-quality situational awareness. These results suggest perceptual error may be a contributor to adverse events in practice.